Microencapsulation of Alkaline Salt Hydrate Melts for Phase Change Applications by Surface Thiol‐Michael Addition Polymerization. Issue 1 (26th April 2012) - Platte, Daniela; Helbig, Uta; Houbertz, Ruth; Sextl, Gerhard
Abstract The microencapsulation of alkaline salt hydrates suitable as inorganic phase change materials (PCMs) via surface Michael‐type addition polymerization of thiols and acrylates is reported. The encapsulation performance depending on the resins' acrylate‐to‐thiol ratio and monomer functionality is investigated, and the best encapsulation performance is found for resin compositions with considerable acrylate excess ratios. The step‐growth nature of the reaction can be substantiated via comparative bulk polymerizations. A multistage encapsulation mechanism is proposed in order to explain the different dependencies on the acrylate to thiol ratio observed in PCM encapsulations in comparison to bulk polymerizations.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>